The Issue of Calculating Elliptic Trajectories - Lozhkin, Alexander; Abramov, Ivan; Bozek, Pavol; Nikitin, Yuri (Manufacturing Technology Journal, 2014)
The design of elliptic trajectories of kinematic mechanisms by classical method is a challenge. New method is proposed. Theoretical tests were conducted on a method. It can not be used for scaling and rotation. Some limitations are revealed as well. Geometric modeling showed the method can be applied to arbitrary curves. It should be noted that the theoretical and modeling researches of arbitary curves is not full. Simple robot was designed for processing ellipses. The design of the stand was assembled from aluminum profiles, linear modules and fasteners RK Rose + Krieger. Experiments have shown a difference between the theoretical and actual trajectory less than 5%. The error of stationing was 8,5% before using of the direct analytical method.
Keywords: Kinematic mechanisms; Geometry; Calculation of trajectory; Arbitrary curves